Women & health / Arutchelvi K. Kumaran, PM Khas Dr Angeline Ranjethemoney Vijayarajoo and Evelyn Shaminie Vasuthevan - K. Kumaran, Arutchelvi; Vijayarajoo, Angeline Ranjethemoney; Vasuthevan, Evelyn Shaminie (UiTM Cawangan Negeri Sembilan, 2022)
Women, as they are called, have to go through all the processes that were created for their role; being a child, attaining puberty, getting married, having kids and finally going through menopause. They take care of their families and rarely have time to spend on themselves and with the passing of time they tend to neglect their health and eventually fall ill to one of the many women-centred health problems. One of the most common health problems that women go through is fibroids. Fibroids are non-cancerous growths that develop in or around the womb (uterus). The growths are made up of muscle and fibrous tissue and differ in sizes. Fibroids can form from the size of a pea (less than 1 cm) to the size of a grapefruit (more than 10 cm). No one knows what causes the fibroids to grow or shrink in size. Although fibroids are usually not dangerous, they can sometimes cause discomfort and even lead to low red blood cells due to the heavy blood loss.